Peningkatan Hasil Belajar IPA Melalui Media Video dengan Model E-Learning pada Siswa Sekolah Menengah Pertama - Ibnu Dwi Kustadiyono (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to improve science learning outcomes in class IX-6 students of SMPN 1 Taliwang for the 2020/2021 academic year by using video media in e-learning. This classroom action research was conducted in class IX-6 SMPN 1 Taliwang in two cycles for 3 months on magnetism material. The research data were obtained through observation and evaluation tests then analyzed descriptively. The results showed an increase in student learning outcomes in each cycle. It can be concluded that the use of video media in e-learning can improve student learning outcomes.